2002
DOI: 10.1097/00004630-200203000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pain in Acutely Burned Children

Abstract: The child with burns suffers severe pain at the time of the burn and during subsequent treatment and rehabilitation. Pain has adverse physiological and emotional effects, and research suggests that pain management is an important factor in better outcomes. There is increasing understanding of the private experience of pain, and how children benefit from honest preparation for procedures. Developmentally appropriate and culturally sensitive pain assessment, pain relief, and reevaluation have improved, becoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 152 publications
0
74
0
8
Order By: Relevance
“…Pesquisadores destacam a importância das atividades lúdicas para as crianças hospitalizadas que são submetidas aos tratamentos dolorosos no corpo (Stoddard et al, 2002). As queimaduras ocasionam nas crianças hospitalizadas mudanças fisioló-gicas e psicológicas que têm repercussões, durante o tratamento, nos seguintes aspectos: relacionamento com a equipe de saúde e a família, dificuldades para reconhecer a importância dos procedimentos técnicos e problemas relacionados à autoimagem.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pesquisadores destacam a importância das atividades lúdicas para as crianças hospitalizadas que são submetidas aos tratamentos dolorosos no corpo (Stoddard et al, 2002). As queimaduras ocasionam nas crianças hospitalizadas mudanças fisioló-gicas e psicológicas que têm repercussões, durante o tratamento, nos seguintes aspectos: relacionamento com a equipe de saúde e a família, dificuldades para reconhecer a importância dos procedimentos técnicos e problemas relacionados à autoimagem.…”
Section: Discussionunclassified
“…A dor representa um fenômeno vivenciado pelos pacientes hospitalizados com queimaduras; dessa forma, o acompanhamento psicológico se torna fundamental para a criança e sua família. Stoddard et al (2002) destacam que as intervenções psicológicas reduzem o nível de estresse da criança hospitalizada e permitem auxiliar o manejo das sensações dolorosas.…”
unclassified
“…The stress of inpatient treatment, specifically a burn dressing change, has been compared with ''inescapable shock'' or ''learned helplessness'' for pediatric burn patients. 31 The Pediatric Acute Wound Service (PAWS) has been developed at our institution, and it allows for inpatient and outpatient surgical management of various soft tissue conditions. We find it to be an ideal unit where traumatic wounds, which otherwise would be historically managed in the operating room or inpatient hospital setting, can be evaluated and managed.…”
Section: Standard Management Of Traumatic Woundsmentioning
confidence: 99%
“…31 Saxe et al showed that one pathway to PTSD was mediated by separation anxiety and this was, in turn, influenced by the acute pain response. 10 Stoddard et al found that parents' acute stress of having a child in pain influenced the child's own acute stress symptoms.…”
Section: Standard Management Of Traumatic Woundsmentioning
confidence: 99%
See 1 more Smart Citation